2000
DOI: 10.1046/j.1524-4725.2000.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Mohs Micrographic Excision of Melanoma Using Immunostains

Abstract: Mohs excision of melanoma using immunostains can be useful, especially for tumors on the head and neck. For routine excision, margins wider than those currently recommended may be required to ensure tumor clearance. We recommend that (1) biopsies be stained preoperatively for Melan-A and/or HMB-45, (2) a debulking layer be obtained for permanent sections prior to Mohs layers, and positive and negative control specimens from the tumor and distant skin should be employed for comparison of staining patterns. Larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
224
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(228 citation statements)
references
References 72 publications
(144 reference statements)
4
224
0
Order By: Relevance
“…The surgical margins for melanoma continue to be debated. The National Institute of Health recommends a 5 mm surgical margin for MIS [21], which is rarely adequate [8,9,22,23]. In 16 cases of LM treated with MMS, a 6 mm margin was adequate for only 23% of cases, and two cases required 1.3 cm margins [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical margins for melanoma continue to be debated. The National Institute of Health recommends a 5 mm surgical margin for MIS [21], which is rarely adequate [8,9,22,23]. In 16 cases of LM treated with MMS, a 6 mm margin was adequate for only 23% of cases, and two cases required 1.3 cm margins [9].…”
Section: Discussionmentioning
confidence: 99%
“…Drawbacks to MMS include the difficulty of histological diagnosis of frozen sections. Modified versions of MMS have developed, using immunostaining [8,9] and rush permanent sections [2,5,[10][11][12] to deal with this difficulty. Successful MMS also requires specific training and experience.…”
Section: Introductionmentioning
confidence: 99%
“…Using Mohs surgery, Robinson 23 found that margins of greater than 6 mm were required to excise 13 (81%) of 16 cases of LM. Zalla et al 24 used Mohs surgery with immunostains and found that only 50% of 46 LM cases were clear with margins of 6 mm or less, while only 71% of 14 LMMs less than 1 mm in Breslow thickness were clear with margins of 10 mm or less. Cohen et al 9 performed Mohs surgery in a series of 45 patients with LM and LMM and found that a mean margin of 13 mm was required for complete excision.…”
Section: Commentmentioning
confidence: 99%
“…In this study, the histopathologic identification of melanoma in situ was aided by immunohistochemical staining of sections with MART-1, a marker for melanocytic differentiation. 7,8,[11][12][13][32][33][34] The increased sensitivity of MART-1 helped enhance the interpretation of specimens at the edge of the area defined by DELM. 8,35 In the hands of an experienced physician, dermoscopy has been shown to increase diagnostic accuracy com- pared with clinical visual inspection.…”
Section: -13mentioning
confidence: 99%